A Review on Design Methods of Vertical take-off and landing UAV aircraft. Issue 1 (April 2021) - Kumar, Veneet; Sharma, Rajkumar; Sharma, Shailesh; Chandel, Siddharth; Kumar, Subodh
Abstract: Unmanned aerial vehicle is the most widely used aircraft technology due to its eminent applications in various fields like in military for surveillance, patrolling and rescue operations, agriculture and civil uses like food delivery, Aerial photography etc. There are two main categories of UAVs; Fixed-wing UAVs and multi-rotor UAVs. There are some issues which arise with conventional aerial vehicles like the absence of enough runway in rural areas and dense forests. Vertical take-off and landing (VTOL) UAVs have the advantages of both fixed-wing and fixed rotor type aircraft. These types of aircraft are more suitable for such applications where lack of runway and dense forests are major issues. This review article mainly focuses on the work done in the domain of design and analysis of vertical take-off and landing (VTOL)